How Do Communication Skills and Emotional Intelligence Influence Students’ Learning? - Sigit Saputra; Agus Hermawan; Reza Ahmadiansah (ANFUSINA: Journal of Psychology, 2023)
The purpose of this study was to determine whether there is an influence of emotional intelligence and interpersonal communication on learning behavior in class X students at SMA Negeri 1 Karanggede Boyolali. The method used in this research is quantitative with the type of causality research. The population used in this study were all students at SMA Negeri 1 Karanggede using simple random sampling technique with a total of 324 students. The sample in this study were 76 students with data collection techniques using the emotional intelligence scale, interpersonal communication scale and learning behavior scale Based on the results of descriptive data analysis on the level of emotional intelligence and interpersonal communication on learning behavior in class X SMA N 1 Karanggede. (1) The level of influence of emotional intelligence on learning behavior in class x students of SMAN 1 Karanggede is in the medium category. Where there is 1 (1.3%) class X student with low emotional intelligence, 39 (51.3%) class X students with moderate emotional intelligence and there are 36 (47.4) class X students who have high emotional intelligence. (2) The level of influence of interpersonal communication on learning behavior in class x students of SMAN 1 Karanggede is in the medium category. Where there were 7 (9.2%) class X students with low interpersonal communication, 49 (64.5) class X students with moderate interpersonal communication and there were 20 (26.3%) class X students who had high interpersonal communication. (3) The level of emotional intelligence and interpersonal communication on learning behavior in class X students of SMAN 1 Karanggede is in the medium category. Where there are 34 (44.7%) students in class X with low learning behavior and there are 42 (55.3%) students in class X who have moderate learning behavior. Based on the results of the analysis of the hypothesis testing data that has been done. It can be seen that the results of f count are 18.455 > 3.12 and the significance value is 0.000 <0.05 and the r-square value is 0.336 or 33.6%. So that it can be interpreted that emotional intelligence and interpersonal communication are acceptable and significant to learning behavior by 33.6% and the remaining 66.4% is influenced by other variables not included in this study. Keywords: emotional intelligence, interpersonal communication, learning behavior